Rethinking the role of mediation in Africa : a decolonial feminist analysis of the Southern African Development Community Regional Strategy on Women, Peace and Security (2018-2022) - Wielenga, Cori (University of Pretoria, 2023)
Mini Dissertation (MA (Diplomatic Studies))--University of Pretoria, 2022.